2018
DOI: 10.21595/vp.2018.20339
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the ride comfort of the off-road vibratory roller cab by adding damper hydraulic mount

Abstract: In order to improve the vibratory roller's ride comfort, a 3-D nonlinear dynamic model of the vehicle interacting with the off-road terrain is established. A damper hydraulic mount is studied and combined with the cab's rubber mounts to simulate and evaluate the performance of the ride comfort. The weighted RMS acceleration responses of the vertical driver's seat, the cab's pitch and roll angle are chosen as objective functions. The results show that the cab's rubber mounts combined with the damper hydraulic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…To evaluate the performance of the damping parameter and installation position of the ADM for reducing vibration of the cab, especially the cab shaking, the weighted RMS accelerations of the vertical driver's seat and pitching cab angle calculated in [9,[14][15] are chosen as the objective functions as follows:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the performance of the damping parameter and installation position of the ADM for reducing vibration of the cab, especially the cab shaking, the weighted RMS accelerations of the vertical driver's seat and pitching cab angle calculated in [9,[14][15] are chosen as the objective functions as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Based on the traditional rubber mount of the vibratory roller cab [1,4], the hydraulic isolation mount used for engine isolation system [6][7][8] were studied and applied for the vibratory rollers to improve the cab ride comfort [1,[9][10]. The results showed that the cab ride comfort with the hydraulic mount was better than the traditional rubber mount.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical values of the EPS are listed in Table 2 In order to analyze the performance of cab hydraulic mounts with PID-Fuzzy control, the reduction of the maximum PSD and weighted RMS accelerations of the vertical driver's seat and pitching cab angle are calculated in [11,21] are chosen as the objective functions. The simulation results of the PSD accelerations of the driver's seat and pitching cab angle with the PID-Fuzzy control at the frequencies of the drum 28 Hz and 35 Hz under the EPS with the low and high-densities are shown in Figs.…”
Section: Numerical Simulation and Results Analysismentioning
confidence: 99%
“…Based on the actual structure of the soil compactor, a nonlinear dynamic model of a single drum vibratory roller with 7DOF is built to evaluate the control performance of the PID-Fuzzy control for cab isolation system equipped with the hydraulic mount (HM) [2,6,11], as plotted in Fig. 1.…”
Section: Dynamic Model and Motion Equationsmentioning
confidence: 99%
See 1 more Smart Citation